Bifidobacterium adolescentis Alleviates Liver Steatosis and Steatohepatitis by Increasing Fibroblast Growth Factor 21 Sensitivity - Long, Xiaoxue; Liu, Dan; Gao, Qiongmei; Ni, Jiacheng; Qian, Lingling; Ni, Yueqiong; Fang, Qichen; Jia, Weiping; Li, Huating (Frontiers in Endocrinology, 2021)
The gut microbiota is a newly identified contributor to the development of non-alcoholic fatty liver disease (NAFLD). Previous studies of Bifidobacterium adolescentis (B. adolescentis), a species of Bifidobacterium that is common in the human intestinal tract, have demonstrated that it can alleviate liver steatosis and steatohepatitis. Fibroblast growth factor 21 (FGF21) has long been considered as a biomarker of NAFLD, and recent studies have shown the protective effect of FGF21 analogs on NAFLD. We wondered whether B. adolescentis treatment would alleviate NAFLD via the interaction with FGF21. To this end, male C57BL/6J mice on a choline-deficient high-fat diet (CDHFD) were treated with drinking water supplemented with B. adolescentis for 8 weeks, followed by the acute administration of recombinant mouse FGF21 protein (rmFGF21) to conduct the FGF21 response test. Consistent with previous studies, B. adolescentis supplementation reversed the CDHFD-induced liver steatosis and steatohepatitis. This was evaluated on the NAFLD activity score (NAS), reduced liver enzymes, and lipid accumulation. Further studies demonstrated that B. adolescentis supplementation preserved the gut barrier, reduced the gut microbiota-derived lipopolysaccharide (LPS), and inhibited the hepatic TLR4/NF-κB pathway. This was accompanied by the elevated expressions of the receptors of FGF21, fibroblast growth factor receptor 1 (FGFR1) and β-klotho (KLB), in the liver and the decreased expression of FGF21. The results of FGF21 response test showed that B. adolescentis supplementation alleviated the CDHFD-induced FGF21 resistance. In vivo experiments suggested that LPS could suppress the expression of FGF21 and KLB in a dose-dependent manner. Collectively, this study showed that B. adolescentis supplementation could alleviate NAFLD by increasing FGF21 sensitivity.